2019
DOI: 10.33581/2520-257x-2019-1-66-77
|View full text |Cite
|
Sign up to set email alerts
|

Novel membranes based on cellulose for gas separation and green method for their preparing

Abstract: A «green» method of obtaining gas separation composite membranes from cellulose solutions and its mixtures with chitosan in orthophosphoric acid is proposed for industrial use, and differs from the viscose method of producing cellophane and other known methods for producing cellulose gas separation membranes without gaseous emissions and wastewater. It is shown that new composite cellulose membranes on a viscose fabric substrate are characterized by high productivity and selectivity for O2/ N2 pairs, comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The amorphization of the cellulose film synthesized from a phosphoric acid solution is evidenced by a decrease in the intensity of the peak at 2θ = 22.4°, which corresponds to the reflection from the (200) crystallographic plane, and the disappearance of the peak at 2θ = 77°, which is responsible for the contribution of crystalline regions to the X-ray diffraction pattern [16]. The authors of [17] compared the degrees of crystallinity of the samples and found that the degree of crystallinity of cellophane and a cellulose film synthesized from a phosphoric acid solution was 65 and 25%, respectively.…”
Section: Analysis Of the Thermomechanical Properties Of The New Compomentioning
confidence: 99%
“…The amorphization of the cellulose film synthesized from a phosphoric acid solution is evidenced by a decrease in the intensity of the peak at 2θ = 22.4°, which corresponds to the reflection from the (200) crystallographic plane, and the disappearance of the peak at 2θ = 77°, which is responsible for the contribution of crystalline regions to the X-ray diffraction pattern [16]. The authors of [17] compared the degrees of crystallinity of the samples and found that the degree of crystallinity of cellophane and a cellulose film synthesized from a phosphoric acid solution was 65 and 25%, respectively.…”
Section: Analysis Of the Thermomechanical Properties Of The New Compomentioning
confidence: 99%